CEO succession and firm performance: Evidence from publicly listed Malaysian firms - Ishak, Rokiah; Ku Ismail, Ku Nor Izah; Abdullah, Shamsul Nahar (Universiti Sains Malaysia, 2013)
This study investigates the impact of CEO succession on the financial performance of publicly listed Malaysian firms.A match-paired t-test and Wilcox on signed-rank test are used to determine if there is a change in firm performance following CEO succession.The overall results show that performance improves following post-succession.We also find significant improvement in the performance of companies that experienced forced turnovers and subsequently selected outsiders as successors.On the other hand, forced CEO turnovers that are followed by internal successions disrupt firm performance.As CEO successions impact firms’ future performance, the succession planning process should be a priority for firms.